Development of Digital-Based Public Information Systems to Enhance Information Quality - Salsabilah; Sihombing, Marlina Br; Tanjung, Muhammad Irvan; Alya, Anggi; Irawan (Proceedings of The International Conference on Computer Science, Engineering, Social Science, and Multi-Disciplinary Studies, 2025)
Digital technology transformation has shifted the paradigm of modern government governance. Public information systems are no longer merely administrative supplements but have become key instruments in achieving openness and accountability. According to Santoso (2025), 'the implementation of digitalization in government is key to increasing transparency and accountability in public governance'. Society now demands public information that is fast, easily accessible, accurate, and transparent; even the Head of BRMP-TROA emphasizes the importance of providing 'public information that is fast, easily accessible, accurate, and transparent'. However, in practice, many public institutions still face obstacles, such as fragmented and poorly integrated information, leading to inconsistent information delivery, delayed responses to public needs, and a lack of efficiency. Digitalization of the public sector is seen as the primary solution to these issues, as technology enables data integration and real-time information presentation with broader access. For example, the use of digital technology allows the government to 'provide greater access to important information for the community, increase participation in decision-making, and accelerate administrative processes'. This literature review synthesizes concepts and previous research regarding public information systems, information quality, and the digitalization of public services. The expected result is a conceptual understanding of how the development of digital-based public information systems can improve the quality of public information and strengthen the principles of transparency and public service effectiveness."